THE IMPACT OF KNOWLEDGE SHARING ENABLERS ON KNOWLEDGE SHARING CAPABILITY: AN EMPIRICAL STUDY ON JORDANIAN TELECOMMUNICATION FIRMS - Raed Kanaan; Ra'ed (Moh’d Taisir) Masa'deh; Ala’a Hamdi Gharibeh (European Scientific Journal, ESJ, 2013)
The aim of this study was to examine the impact of knowledge sharing enablers on knowledge sharing capability. This study used a questionnaire where the scale is adapted to measure those dimensions of knowledge sharing enablers (i.e. enjoyment in helping others, knowledge self-efficacy, top management support, organizational rewards, and ICT use) and knowledge sharing capability. This study targeted the telecommunication companies in Jordan, namely Orange and Umniah. The suitable returned questionnaires accounted for 367 out of 600. Multiple regression analysis was used to explore the impact of each of the knowledge sharing enablers on knowledge sharing. This study found that knowledge sharing enablers affect knowledge sharing. Also, it found that the most influential dimension of knowledge sharing was enjoyment in helping others; followed by ICT use, organizational rewards, and then top management support. However, knowledge self-efficacy did not have a statistically significant effect over knowledge sharing.